K-MEANS ALGORITHM DATA MINING IN SALES LEVEL ANALYSIS - Nofri Yoliadi, Dodi (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2022)
In this research, data collection and processing of sales of electronic goods were carried out with CV. Berkah Elektronik. The data obtained is then aggregated with the K-Means algorithm to gain knowledge about which electronic products are selling well on the market and which are not. In this study, the clustering method was used with Tanagra 1.4.48 software, and the K-Means algorithm was used as an algorithm to draw conclusions about which items were selling well and which were not inputted, namely product prices. goods and sale of goods. And from the results of testing and manual testing with the Tanagra application, the same clusters are produced, namely, products that do not sell well (Cluster_KMeans_1) and products that sell well (Cluster_KMeans_2).